EFFECTIVENESS OF DIGITAL MARKETING ON UNPLANNED PURCHASING BEHAVIOUR AMONG GEN Z - Steven, Steven (GEMAH RIPAH: Jurnal Bisnis, 2025)
Generation Z in Indonesia is particularly susceptible to digital marketing, often leading to spontaneous and unplanned purchases. This study investigates the influence of perceived ease of use and perceived usefulness of digital marketing platforms on emotional responses and how these emotions affect impulsive buying behaviour. Guided by the Stimulus-Organism-Response (S-O-R) theoretical model, this quantitative research involved 153 Gen Z respondents. Data were collected through online surveys distributed via social media platforms and analyzed using multiple regression and path analysis. The results demonstrate that perceived ease of use and usefulness significantly enhances emotional responses, increasing the likelihood of impulsive purchases. Additionally, the study confirms a direct positive effect of emotions on impulsive buying. However, the mediating role of emotion between the two predictors and impulsive buying was not statistically significant, implying that direct relationships are more impactful. These findings emphasize the critical role of user-friendly and value-driven digital marketing in encouraging purchase decisions among Gen Z, particularly when emotional responses are effectively triggered. The study contributes to the growing research on consumer psychology in digital contexts. It provides insights for marketers aiming to design strategies that appeal to younger audiences’ emotional and technological preferences.